The impact of the emergency response to the outbreak of the cassava mosaic disease in the Democratic Republic of Congo - Rusike, Joseph; Mahungu, N.M.; Lukombo, S.S.; Kendenga, T.; Bidiaka, S.M.; Alene, A.; Lema, A.; Manyong, Victor M. (International Society for Tropical Root Crops, 2012)
This paper evaluates the impact of an emergency research for development project implemented in the Democratic Republic of Congo from 2000 to 2009 by a various actors including the International Institute of Tropical Agriculture in response to the outbreak of the Cassava Mosaic Disease that threatened the national food security. It applies methods developed in the econometric and statistical treatment effects literature on evaluation of social programs. The study evaluates impact by analyzing changes over time of outcomes of sample households in the project areas compared to neighboring non-project areas. We find that the project had statistically significant positive effects on technology adoption, area planted cassava, productivity, profitability,household food security and aggregate supply response. The effects are strongest among lower tails of distribution of outcomes mostly made up of female-headed households who grew the crop mainly for food. These findings are useful for informing agricultural and food policy debates in Africa.